The Development Study of Madura Area (An Area Marketing Approach) - Nurif, Muchammad; Hermanto, Hermanto (Institut Teknologi Sepuluh Nopember, 2019)
The development of Madura area has its own challenge due to its low development indicators which become the complexity barometer of development problems in this area. The development of Madura area has main obstacles, such as the limitation of infrastructure and transportation acces from and to Madura that weakens the economic development in this area. However, there are many promising potentials of the island that can be developed although until now because of its limitation, the development of Madura is not yet optimal. This research used area marketing concept called Strategic Place Triangle model with nine elements that are categorized into three dimensions, namely strategic (segmentation, targeting, positioning), tactic (differentation, marketing mix, and selling), and value (brand name, service, and process). The data that is used in this research is primary data (derived from questionnaries), and secondary data from some related institutions. The conclusion of the research showed that resource-based industrial sectors (agricultural and natural industries) are the recommended sectors that shall be developed in Madura area. While the segmentation result showed that there were two main investors, namely PMDN and Non Facility. PMDN investors tend to invest in agricultural-intensive resources and labor intensive (Sumenep and Pamekasan districts), whereas Non Facility investors tend to invest in natural- intensive resorces (Bangkalan and Sampang districts). Compared to its main competitor, Sidoarjo district, Madura has some added-value, such as inexpensive price of land, investment opportunity, loading and unloading harbor in Bangkalan district, and agricultural and natural resources for industry.